ANALISIS RELEVANSI NILAI ATAS LABA AKUNTANSI, NILAI BUKU EKUITAS, ASET KEUANGAN, DAN LIABILITAS KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 - Dava Rahma Satria Wibawa; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the value relevance of earnings, equity book value, financial assets, and financial liabilities to stock prices in LQ45 Index companies on the Indonesia Stock Exchange from 2017 to 2020. The measurement model in this study uses the Ohlson (1995) price model to see the effect of earnings, book value of equity, financial assets, and financial liabilities to stock prices. This study uses 30 LQ45 Index companies on the Indonesia Stock Exchange which had been selected using the purposive sampling method. The type of data used in this study is secondary data that can be accessed through the websites of the Indonesia Stock Exchange, Stockbit, and Yahoo Finance. Based on the results of the tests, earnings measured with the earnings per share (EPS) ratio and book value measured with the book value per share ratio (BVPS) have proven to have a positive and significant effect on stock prices. Meanwhile, financial assets and financial liabilities proved to be insignificant to the stock prices of LQ45 Index companies from 2017 to 2020. So it can be concluded that earnings and book value have value relevance because they contain information needed by investors in investment decision.